ANALISIS KINERJA ASISTEN TENAGA KESEHATAN FARMASI DI APOTEK WILAYAH KOTA TEGAL SESUAI DENGAN PERMENKES RI NOMOR 80 TAHUN 2016 TENTANG PENYELENGGARAAN PEKERJAAN ASISTEN TENAGA KESEHATAN - Akhmad Aniq Barlian; Meliyana Perwitasari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
In playing its role and function, a pharmacy cannot be alone. Pharmacists need the role of other fields that are able to manage or carry out their functions and roles to the maximum, namely pharmacists. Thus, the pharmacy becomes very dependent on the pharmacist who can run all the pharmacy's work. Therefore a pharmacist in carrying out his duties can be assisted by several technical personnel namely assistant pharmacist (AA). The purpose of this study was to determine the performance of pharmacist assistant (AA) graduates of pharmacy school graduates in the pharmacy area of Tegal city in accordance with the Republic of Indonesia Minister of Health Regulation No. 80 of 2016 concerning the Implementation of Health Workers Assistant Work. and compare with existing regulations, and analyze the reasons for not implementing the regulations. The results of the study aimed that the majority of pharmacy fitness assistants had carried out work in accordance with the Republic of Indonesia Minister of Health Regulation No. 80 of 2016 concerning the Implementation of Health Workers Assistant Work. Namely Recording About Purchasing and Storage of Medicines As well as Collecting Drug Inventories with 100% results, Receiving Payment of Prescriptions, Stock Prices, Marking Items for Sales, Recording and Insurance Claims with 100% results, Household Health Supplies Services with 100% results, Prescription Archiving In Accordance with Data and Conditions Valid with 100% results, Examination of Suitability of Pharmaceutical and Medical Supplies Orders with 92.86% results. Keyword : Pharmacy, Pharmacist Assistant, Pharmacy Work